Kualitas Pelayanan Penanganan Pengaduan Pelanggan di Perusahaan Umum Daerah Air Minum Mojopahit (PERUMDAM) Mojopahit - Wardani, Adinda Maulina Kusuma; Tukiman (Universitas Djuanda, 2025)
Quality is an essential thing in service to determine the feasibility of a company or organization in providing services. Customer assessment of public services is one of the determinants of the quality of services provided. One form of customer assessment is customer complaints regarding the services received and how complaints are handled. Mojokerto Regency Mojopahit Drinking Water Company, as a clean water provider for the community, also serves complaints about service delivery. This study aims to determine, explain, and analyze the quality of service for handling customer complaints at the Mojokerto Regency Drinking Water General Company. This research focuses on the dimensions of service quality proposed by Parasuraman. The research method used is a descriptive qualitative method. The data collection techniques used are interviews and observations to obtain qualitative data and documentation to obtain a valid field picture. The results showed that the quality of service for handling customer complaints at the Mojokerto Regency Mojopahit Drinking Water General Company using Parasuraman's service quality dimensions in the dimensions of tangibles, reliability, and empathy is already qualified, so it is necessary to maintain the quality of service that has been provided. In contrast, the dimensions of responsiveness and assurance are not yet qualified, so it is necessary to improve the quality of service that has not been implemented optimally.